The role of MgF2 in the development of spark plasma sintered transparent MgAl2O4 ceramics; Ceramics International; Vol. 52, iss. 6 - Paygin V. D. Vladimir Denisovich; Huang Fuli; Deulina D. E. Darjya Evgenjevna; Stepanov S. A. Sergey Aleksandrovich; Dvilis E. S. Edgar Sergeevich; Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Shevchenko I. N. Ivan Nikolaevich (2026, 2026)
Title screen